Identification of Cadmium and Lead in Cocoa crops located in the Satipo - Junin zone - Rosales Huamani, Jimmy Aurelio (2021)
The concentration of heavy metals in cocoa crops is currently a serious problem for farmers and producers in various regions of Peru. Exports of cocoa and its derivatives to European markets are threatened by possible evidence of heavy metal contamination in exportable cocoa beans, some at levels higher than those permitted by food regulations established by the European Community, which are aimed at protecting consumers. It is considered that the possible reasons for the contamination of the Cd in cocoa crops may come from natural activities such as volcanic activities, erosion processes and sedimentation in rocks that contain minerals with a high content of these heavy metals. This contamination is also produced by anthropogenic activities such as mining of associated deposits, agriculture (use of fertilizers), smelting of minerals and burning of fossil fuels. Currently, there is no information about the content of heavy metals such as Cadmium (Cd) and Lead (Pb) in a study area located in Satipo-Junin. In this work, we study this region, using a methodology to obtain the concentrations of Cd and Pb metals present in the soil of foreign-type cocoa crops. As a consequence of this study we determined and concluded that the concentrations obtained of Cd and Pb in soils are inferior to the standards established by the Ministry of Environment (MINAM), in addition we generated the geochemical map of the study zone with these metals.